Embryonic Development of the Gastrodermis in the Coral Acropora tenuis - Kawamura, Kaz; Satoh, Noriyuki (Zoological science, 2024)
Due to limited spawning seasons, embryogenesis of corals has not fully been studied and the embryonic origin of gastrodermis remains uncertain in . We herein examined how embryonic endodermal cells develop into the gastrodermis and mesentery of polyps in . In juvenile polyps, the gastrodermis invaginates to form mesenteries, both of which were stained with rhodamine-phalloidin, an anti-myocyte-specific enhancer factor 2 (anti-AtMef2) antibody, and an anti-lipoxygenase homology domain-containing protein 1 (anti-AtLoxhd1) antibody. Rhoda-mine-phalloidin staining was traced back to the endodermal cells of 60-85 hpf 'pear'-stage embryos through the larval stage. AtMef2 appeared in the blastomeres of a 12-hpf 'prawnchip'-stage embryo that was a variant U-shaped blastula with a narrow blastocoel. AtMef2 temporarily disappeared from the nuclei of 28-hpf 'donut'-stage embryos and reappeared in the endodermal cells of 40-hpf early 'pear'-stage embryos, suggesting a transition from maternal to zygotic expression of Mef2. The blastopore closed without the invagination of blastomeres. The gastrocoel collapsed and the Mef2-positive endoderm was dissociated into single cells in the well-developed blastocoel filled with yolk cells. The mesoglea appeared in the yolk cell layer. AtLoxhd1 was traced back to the endodermal cells of 'pear'-stage embryos. In 11-dpf larvae, Loxhd1-positive endodermal cells elongated in the vicinity of the mesoglea to adhere to each other and form the gastroderm epithelium in larvae. Therefore, in this coral, the inner wall of U-shaped early embryos is the cellular origin of the gastrodermis. Inner wall-derived endodermal cells move independently toward the mesoglea, where cell-cell adhesion occurs to establish the gastrodermis.